Engaged Urban Pedagogy Participatory practices in planning and place- making - Natarajan, Lucy; Short, Michael (Engaging Communities in City-making, 2023)
Engaged Urban Pedagogy presents a participatory approach to teaching built environment subjects by exploring 12 examples of real-world engagement in urban planning involving people within and beyond the university. Starting with curriculum review, course content is analysed in light of urban pasts, race, queer identity, lived experiences and concerns of urban professionals. Case studies then shift to focus on techniques for participatory critical pedagogy, including expanding the 'classroom' with links to live place-making processes, connections made through digital co-design exercises and student-led podcasting assignments. Finally, the book turns to activities beyond formal university teaching, such as where school-age children learn about their own participation in urban processes alongside university students and researchers. The last cases show how academics have enabled co-production in local urban developments, trained community co-researchers and acted as part of a city-to-city learning network. Throughout the book, editorial commentary highlights how these activities are a critical source of support for higher education. Together, the 12 examples demonstrate the power and range of an engaged urban pedagogy. They are written by academics, university students and those working in urban planning and place-making. Drawing on foundational works of critical pedagogy, they present a distinctly urban praxis that will help those in universities respond to the built environment challenges of today.